An Italian Case of Disseminated Histoplasmosis Associated with HIV - Chiara Papalini; Barbara Belfiori; Giovanni Martino; Rita Papili; Lucia Pitzurra; Stefano Ascani; Maria Bruna Pasticci (Case Reports in Infectious Diseases, 2019)
Histoplasma capsulatum is a dimorphic fungus, endemic in the Americas, Africa (var. duboisii), India, and Southeast Asia. H. capsulatum infection is rarely diagnosed in Italy, while in Latin America, progressive disseminated histoplasmosis (PDH) is one of the most frequent AIDS-defining illnesses and causes of AIDS-related deaths. We report a case of PDH and new HIV infection diagnosis in a Cuban patient, who has been living in Italy for the past 10 years. Bone marrow aspirate and peripheral blood smear microscopy suggested H. capsulatum infection. The diagnosis was confirmed with the culture method identifying its thermal dimorphism. Liposomal amphotericin B was administered alone for 10 days and then for another 2 days, accompanied with voriconazole; the former was stopped for probable side effects (persistent fever and worsening thrombocytopenia), and voriconazole was continued to complete 4 weeks. PDH maintenance treatment consisted of itraconazole for one year. Antiretroviral therapy (ART) was started on the third week of antifungal treatment. At the 3-year follow-up, the patient is adherent on ART, the virus was suppressed, and she has an optimal immune recovery. This case highlights the need to suspect histoplasmosis in the differential diagnosis of opportunistic infections in immunocompromised persons, native to or who have traveled to endemic countries.